Response of cassava to VA mycorrhizal inoculation and phosphorus application in greenhouse and field experiments - Howeler, Reinhardt H.; Cadavid, L.F.; Burckhardt, E (Springer, 1982)
Cassava (Manihot esculenta Crantz) was grown in the greenhouse and in the field at different levels of phosphorus applied, with or without inoculation with VA mycorrhiza in sterilized or unsterilized soil. When grown in a sterilized soil to which eight levels of P had been applied the non-inoculated plants required the application of 3200 kg P ha?1 to reach near-maximum yield of plant dry matter (DM) at 3 months. Inoculated plants, however, showed only a minor response to applied P. Mycorrhizal inoculation in the P check increased top growth over 80 fold and total P uptake over 100 fold. Relating dry matter produced to the available P concentration in the soil (Bray II), a critical level of 15 ppm P was obtained for mycorrhizal and 190 ppm P for non-mycorrhizal plants. This indicates that the determination of critical levels of P in the soil is highly dependent on the degree of mycorrhizal infection of the root system. In a second greenhouse trial with two sterilized and non-sterilized soils it was found that in both sterilized soils, inoculation was most effective at intermediate levels of applied P resulting in a 15 30 fold increase in DM at 100 kg P ha?1. In the unsterilized soil inoculation had no significant effect in the quilichao soil, but increased DM over 3 fold in the Carimagua soil, indicating that the latter had a native mycorrhizal population less effective than the former. When cassava was grown in the field in plots with 11 levels of P applied, uninoculated plants grown in sterilized soil remained extremely P deficient for 4 5 months after which they recuperated through mycorrhizal infection from unsterilized borders or subsoil. Still, after 11 months inoculation had increased root yields by 40%. In the non-sterilized soil inoculation had no significant effect as the introduced strain was equally as effective as the native mycorrhizal population. These trials indicate that cassava is extremely dependent on an effective mycorrhizal association for normal growth in low-P soils, but that in most natural soils this association is rapidly established and inoculation of cassava in the field can only be effective in soils with a low quantity and quality of native mycorrhiza. In that case, plants should be inoculated with highly effective strains.